Development Monopoly Quiz for Increase Awareness Culture and Thinking Critical : Literature Study - Dienti, Lulu Sania; Raharjo, Tri Joko; Khafid, Muhammad; Subali, Bambang; Widiarti, Nuni (Journal of Educational Sciences, 2025)
The implementation of the Merdeka Curriculum in Indonesia requires an evaluation of teaching materials, including textbooks, to ensure alignment with the principles of the curriculum, but systematic research on textbook analysis is still limited. This research aims to identify research trends in the analysis of elementary school student books under the Merdeka Curriculum during the period 2020-2025. Using the Systematic Literature Review (SLR) method, the researchers analyzed 5 journal articles and proceedings indexed in Google Scholar published between 2020-2025, focusing on studies of the analysis of Indonesian language textbooks for elementary school students. The research findings indicate: (1) an increasing trend in research on the analysis of Merdeka Curriculum textbooks, (2) the dominance of Universitas Negeri Semarang as the most active institution in this field, and (3) a diversity of analytical instruments used according to the individual objectives of each study. The study's conclusion underscores the importance of raising awareness among educators and researchers in evaluating the feasibility of textbooks, as well as the need for the development of more consistent analysis standards.